Nursing Care in Tn. B And Tn. S with Disorders of Sensory Perception: Hallucinations - Asmarita; Mahendra, Mahesa (Yayasan Rumah Ilmu Professor, 2023)
This study aims to explain and evaluate the implementation of nursing care for patients who experience auditory hallucinations. The research method uses a case study approach by collecting data from initial assessments, nursing diagnoses, care plans, nursing interventions, evaluations, and discharge planning. The research results show that an initial assessment is carried out by identifying mental health history, behavior related to hallucinations, and triggering factors that may influence the patient's condition. The nursing diagnosis was determined as sensory perception disorder: auditory hallucinations. The treatment plan involves collaboration with the mental health team, behavioral monitoring, emotional support, and education of the patient and family. Nursing interventions include explanation of the nature of hallucinations, assistance in identifying reality, and use of relaxation and distraction techniques. Evaluations are carried out to assess the patient's response to the interventions provided and monitor changes in the intensity or frequency of hallucinations, discharge planning and provide information regarding warning signs. Conclusion: Nursing care for patients with sensory perception disorders requires a holistic approach and collaboration between nurses and the mental health team. Education for patients and families also has an important role in supporting the management of this condition.